Impact of Tax Avoidance, State Ownership, Foreign Ownership, and Firm Size to Firm Value in Indonesia - Sindy Sindy; Dea Tiara Monalisa Butar-Butar (Faculty of Economics, Universitas Internasional Batam, 2023)
Purpose - The objectives of the research are to identify and verify the effect of tax avoidance on firm value in Indonesia. State ownership, foreign ownership, company size also influences the value of companies in Indonesia. This study argues that tax avoidance and other elements do not necessarily add value to Indonesian firms. Research Method - This study uses data from companies registered as LQ45 in the period 2017-2021. Taking the research sample is a purposive sampling method. The population of companies listed on IDX is 810 companies, which 45 companies are included in the LQ45 sample with a total sample data of 225. After conducting outliers, 225 data samples are obtained. This study uses a comparative causal method. Research data processing was executed with the help of the Eviews 10 applications. Findings - The outcomes of this paper prove that tax avoidance, state ownership and foreign ownership have no significant effect on firm value while firm size has positive effect on firm value. Implication - This research is expected to contribute to the expansion of knowledge, especially in the field of accounting. The study is intended to provide information about the factors that affect the value of the company and evaluate matters relating to company value.